The Burden of Asthma in Oman - Nasser Al-Busaidi; Zulfikar Habibulla; Malvika Bhatnagar; Nabil Al-Lawati; Yaqoub Al-Mahrouqi (Sultan Qaboos University Medical Journal, 2015)
Asthma is a common lung disease worldwide, although its prevalence varies from country to country. Oman is ranked in the intermediate range based on results from the International Study of Asthma and Allergies in Childhood. A 2009 study revealed that the majority of asthmatic patients in Oman reported both daytime and nocturnal symptoms, while 30% of adults and 52% of children reported absences from work or school due to their symptoms. Despite these findings, there is little data available on the economic burden of asthma in Oman. The only accessible information is from a 2013 study which concluded that Oman’s highest asthma-related costs were attributable to inpatient (55%) and emergency room (25%) visits, while asthma medications contributed to less than 1% of the financial toll. These results indicate a low level of asthma control in Oman, placing a large economic burden on healthcare providers. Therefore, educating asthmatic patients and their families should be prioritised in order to improve the management and related costs of this disease within Oman.